Understanding the reason for Malaysian youth participation in volunteering activities - Hamzah, Siti Raba’ah; Suandi, Turiman; Arif Shah, Jasmin; Ismail, Ismi Arif; Hamzah, Azimi (Athens Institute for Education and Research, 2016)
This paper explores the reasons for Malaysian youth participating in volunteering activities and examines the variables that predict their participation. The subjects used in the study were from the Department of Youth and Sports, Malaysia. A total of 251 respondents, between the ages 15 to 25 (M age = 20.2, SD = 2.7), participated in this study. Using the Social Exchange theory as a framework for this study, three main factors contributing to youth participation in volunteering activities were the perceived benefits from volunteering ("benefits") , the personal needs or fulfillment of the respondents to volunteer ("needs"), and their personal reasons for volunteering ("reasons"). Our findings showed that the "benefits" included learning to shoulder responsibility, broadening interest, fostering relationships, building teamwork spirit, and encouraging socialisation within the community setting. The "need" to volunteer was associated with the desire to unleash leadership potential and improve communication skills. Finally, the "reasons" for volunteering included using leisure time meaningfully, getting new experience, improving confidence and self-esteem, attaining emotional stability, and getting a better understanding of the realities of life. The findings indicated positive relationships between the participation and "benefits", "needs" and "reasons" to volunteer. However, "reason" was the strongest predictor of the youth becoming volunteers.